The Role of Cognitive Emotion Regulation for Making and Keeping Friend and Conflict Networks - Ricciardi, Courtney; Kornienko, Olga; Garner, Pamela W. (Frontiers in Psychology, 2022)
We used social network analysis (SNA) to examine how adaptive ER strategies (acceptance, positive reappraisal, refocusing, and putting in perspective) and maladaptive ER strategies (rumination, catastrophizing, self- and other-blame) predict the creation and maintenance of friendship and conflict relationships within a mixed-gender social group. Participants (n = 193, 53% female, M age = 19.4 years, 62.1% White) reported on emotion regulation, friendship, and conflict nominations at two time points. Stochastic actor-oriented models revealed that similarity in endorsement of adaptive ER strategies predicted maintenance of friendship and conflict relationships over time. However, new conflict relationships were more likely to form between those who differed in use of adaptive ER. Finally, more frequent use of maladaptive ER strategies was related to termination of existing conflict ties and the creation of new ones. Deploying social network analysis as a methodology for examining social relationships enables the unpacking the dynamics of multiple social relationships (friend, conflict), identifying the role of ER for structuring of social relationships among group members. Although cognitive ER is an intra-individual process, it fundamentally occurs within a social environment and our results advance the knowledge of how ER contributes to how this social environment is created in a first place.